The Impact of Covid-19 Pandemic to Palm Oil Companies Stock in Indonesia - Bancin, Hardi Dominikus; Dolorosa, Eva; Yurisinthae, Erlinda (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The purpose of this study was to analyze the differences in the average abnormal return, the average trading volume of activity, and the average bid-ask spread on the stock of oil palm companies in Indonesia before and after the announcement of New Normal in Indonesia and the opening of lockdown in the country export destination. In this study, three countries were taken by the Netherlands, Malaysia, and Singapore. 13 companies sampled in this study are determined using purposive sampling techniques. The data used in this study are secondary data accessed by researchers through the Yahoo Finance website and the Indonesia Stock Exchange. The variables used in this study are abnormal returns, trading volume activities, and bid-ask spreads. The testing carried out in this study used a paired t-test and tested Wilcoxon test. The results of this study indicate: (1) The results of statistical testing on the average abnormal return during the event, there is a difference in the normal new event in Indonesia, the opening of lockdown in the Netherlands and Singapore. The average value of the abnormal return is positive, so it can be concluded that this event is categorized as good news. (2) The results of statistical testing on the average trading volume activity during the event show a difference in the opening of the lockdown in Malaysia. (3) The results of testing at the average bid-ask spread during the event show a difference in the opening of the lockdown in Malaysia. Keywords: Covid-19, palm oil, abnormal return, trading volume activity, bid-ask spread